The precautionary priciple in biodiversity conservation and natural resource management (An issues paper for policy-makers, researchers and practitioners) / Rosie Cooney - Cooney, Rosie (Switzerland: IUCN, 2004)
The context of this study, background and objectives, the meaning of the precautionary principle, the core concept of precaution, the content of the precautionary principle precaution, prevention, and polluter-pays, precaution and science, acceptance of the precautionary principle in biodiversity and natural resources law and policy, development of the principle in environmental law and policy biodiversity and general environmental law and policy fisheries law and policy forest law and policy, implementing precaution in biodiversity and natural resource management: issues and challenges, does acceptance of the principle in law and policy translate into implementation? what sectoral features shape the implementation of precaution in biodiversity and natural resource management? through what tools and approaches can precaution be implemented?, assessing conservation costs and benefits, costs, benefits, and competing objectives; the balancing act of implementing precaution
Portada ilustrada, index, references
Col. Agrof
Keywords: 1. CONSERVATION-PROTECTION 2. BIODIVERSITY-CONSERVATION 3. NATURAL RESOURCE 4. AGROFORESTRY